On the role of ocean-atmosphere interaction in midlatitude interdecadal variability - Weng, Wenjie; Neelin, J. David (Geophysical research letters, 1998)
A simple midlatitude ocean‐atmosphere model is used to investigate possible roles of coupled feedback in interdecadal climate variability over the North Atlantic and North Pacific oceans. Stochastic forcing by atmospheric internal variability maintains variance in both uncoupled and coupled cases. Coupling contributes to creating an interdecadal mode with distinct spatial pattern and preferred time scale, seen as a broad spectral peak. A near‐analytic solution for the coupled interdecadal mode suggests that the most important parameter in determining the period is the zonal length scale of the atmospheric wind stress feedback over the region. Subject to this scale, the period is then determined by oceanic Rossby wave dynamics, which tends to give westward propagation in subsurface fields. The dipolar sea surface temperature (SST) anomalies are generated primarily by the advection of climatological SST by geostrophic current. Although the magnitude of the feedback of SST to atmospheric response is much smaller than atmospheric internal variability, its effects are significant.